Raising the contraceptive prevalence rate to 50% by 2025 in Pakistan: an analysis of number of users and service delivery channels - Mujahid Abdullah; Faiq Bilal; Romesa Khan; Azadeh Ahmed; Aamir Ashraf Khawaja; Faisal Sultan; Adnan Ahmad Khan (BMC, 2023)
Abstract Background Pakistan is the fifth most populous country in the world, with a population that is growing at 2.4% annually. Despite considerable political will, including a national commitment that was endorsed by the president to raise the contraceptive prevalence rate (CPR) to 50% by 2025, it has stagnated at around 30-35%. Much of the dialogue on raising CPR is hypothetical and revolves around percentage point change rather than an actual number of women that must be served. Methods The Demographic and Health Survey 2017-18 (DHS 2017-18) provides information about the channels through which users receive family planning (FP) services and disaggregates this information at the provincial level. Proportions of users from each of these channels were multiplied by the Pakistan Census-2017 populations to arrive at the number of users. These users were compared with the total FP users and the number of women that had used any FP service in the past 12 months. Linear estimations of population were applied to calculate population numbers in 2025. Results The national target of 50% CPR by 2025 translates to a population of 20.02 million users. Currently, 11.26 million married women of reproductive age (MWRA) use any method, 8.22 million use a modern method and 4.94 million received this service in the past 12 months. Of these, 2.7 million did so from social marketing outlets, 0.76 million from public sector outreach through lady health workers (LHWs), 0.55 million from private sector and 0.88 million from public sector facilities. However, arriving at the CPR target means expanding annual service delivery from 4.94 to 13.7 million users. Since social marketing and LHW outreach may have become saturated, only public and private health facilities are the likely channels for such an expansion. Conclusions We demonstrate triangulation of the survey data with the census data as a simple policy analysis tool that can help decision-makers estimate the quantum of services they must provide. Such an analysis also allows an understanding of the utilization patterns of each of these channels. In Pakistan's context, underutilization of funds and existing facilities suggests that increased funding or more providers will likely not be helpful. The policy changes that will likely be most effective include adding outreach to support existing public and private sector facilities while ensuring that procurement of commodities is prioritized.